2004
DOI: 10.1007/s00405-004-0827-8
|View full text |Cite
|
Sign up to set email alerts
|

The pectoralis myofascial flap in pharyngolaryngeal surgery after radiotherapy

Abstract: Pharyngocutaneous fistula after total laryngectomy remains a hardly inevitable complication. The predisposing factors are not clearly identified, but prior radiotherapy seems to increase the risk of fistulae. The purpose of this retrospective study was to determine the value of the pectoralis myofascial flap in pharyngeal reconstruction in post-radiotherapy total laryngectomy in order to decrease the risk of fistula formation. The charts of 60 consecutive patients who had undergone total laryngectomy or pharyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
1
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 19 publications
4
87
1
5
Order By: Relevance
“…The principle behind using this so-called pectoralis major myofascial flap (PMMFF) is that healthy tissue with abundant vascularity will improve wound healing and prevent local wound complications, including PCF. Righini et al [10] reported a reduction in PCF risk after salvage surgery from 50 to 23% using PMMFF; Gil et al [11] on the other hand found no significant decrease in PCF risk using PMMFF. However, in all cases, PCF was conservatively closed.…”
Section: Discussionmentioning
confidence: 99%
“…The principle behind using this so-called pectoralis major myofascial flap (PMMFF) is that healthy tissue with abundant vascularity will improve wound healing and prevent local wound complications, including PCF. Righini et al [10] reported a reduction in PCF risk after salvage surgery from 50 to 23% using PMMFF; Gil et al [11] on the other hand found no significant decrease in PCF risk using PMMFF. However, in all cases, PCF was conservatively closed.…”
Section: Discussionmentioning
confidence: 99%
“…Another fistula-preventive strategy is the insertion of nonirradiated, well-vascularized tissue; therefore, many authors have described the use of PM flap reconstruction in a salvage setting. Righini et al 16 performed a study examining the use of the PM flap and noted a substantial reduction in fistula rate, from 50% to 23%. This difference, however, did not reach statistical significance.…”
Section: Commentmentioning
confidence: 99%
“…These flaps can be quickly fashioned, are viable and reliable, versatile in reconstruction procedures, located close to the site of resection, and allow the reconstruction to be done in one single procedure with low complication rates on the donor site [18][19][20] . When used in salvage laryngectomy, the myocutaneous flap may reduce salivary fistula incidence rates from 24% to 0% (p < 0.015), as shown by Patel & Keni 8 , and from 51% to 20% (p < 0.028) according to Righini et al 21 . In our study, the incidence of salivary fistulas in myocutaneous flap patients was 16%, while primary laryngeal closure patients had a salivary fistula incidence rate of 58%.…”
Section: Discussionmentioning
confidence: 90%
“…As it is a regional flap, it does not require specific materials or teams specialized in microsurgical anastomoses; and it introduces low donor site morbidity 2,21 . Myocutaneous flaps could also reduce the risk of late complications such as stenosis, dysphagia, and use of feeding tubes as shown by Patel & Keni 8 ; these findings were not observed in our study.…”
Section: Discussionmentioning
confidence: 99%